110k views
4 votes
Y= 2/3x -1 y= -x + 4

User StevieD
by
4.7k points

2 Answers

3 votes

Answer:

The solution is x = 3 and y = 1.

Explanation:

We have given a system of equations.

y= 2/3x -1 eq(1)

y= -x + 4 eq(2)

We have to find the solution of given equations.

Equating above of equations, we have

2/3x-1 = -x+4

2/3x+x = 4+1

5/3x = 5

5x = 15

x = 3

Putting the value of x in eq(2), we have

y = -3+4

y = 1

Hence, the solution is x = 3 and y = 1.

User Sandeep Datta
by
4.5k points
5 votes

Answer:


x=3\\y=1

Explanation:

To solve the system of equations you must apply the proccedure shown below:

- Make both equations equal to each other.

- Solve for x.

Then:


(2)/(3)x-1=-x+4\\\\(2)/(3)x+x=4+1\\\\(5)/(3)x=5\\5x=5*3\\x=(15)/(5)\\\\x=3

- Substitute the value of x obtained into any on the original equations to find y:


y=-3+4\\y=1

User Shagun Pruthi
by
4.6k points